Determination of the mass fraction of potassium and sodium oxides in the dust of electric furnace filters by atomic emission spectrometry with inductively coupled plasma - V. A. Makarov; T. K. Savosteenko (Литьë и металлургия)
A method of measuring the mass fraction of potassium and sodium oxides in the dust filters of electric arc furnaces by atomic emission  spectrometry  with  the  inductively  coupled  plasma  (AES-ICP)  was  developed.  Possibilities  of  atomic  emission spectrometers of iCAP series for determination of potassium and sodium in dust of filters of electric arc furnaces are investigated.A method for converting potassium and sodium oxides into solution is proposed. Calibration of the spectrometer was carried out on aqueous solutions with a known concentration of potassium and sodium. For the preparation of calibration solutions, chemically pure potassium and sodium salts were used. Analytical lines of potassium and sodium free from spectral overlays are selected.A good correlation of calibration graphs is obtained. The developed technique is used to determine the mass fraction of potassium and sodium oxides in the dust filters of electric furnaces. Validation of the methodology was carried out. The repeatability of the results was compared with the repeatability of the standardized methodology. iCAP series spectrometers can be used to determine the mass of potassium and sodium oxides in gas cleaning dust.s cleaning dust.